The Role of Strategic Monitoring in Enhancing Strategic Response: An Analytical Study of the Opinions of a Sample of Managers in a Number of Delivery Companies in the Kurdistan Region – Iraq. - Mohammed, Mohammed Abdulqader (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Strategic management increasingly emphasizes organizational capability to respond to dynamic and uncertain environments, particularly within service sectors such as delivery companies. Specific Background Delivery firms in the Kurdistan Region–Iraq face challenges in addressing evolving customer demands, technological changes, and competitive pressures, requiring stronger strategic response mechanisms. Knowledge Gap Despite recognition of strategic monitoring as a modern managerial approach, limited empirical evidence exists on how its dimensions contribute to strategic response in delivery companies. Aims This study aims to examine the role of strategic monitoring comprising strategic intelligence, strategic thinking, and strategic vigilance in strengthening strategic response, including resource fluidity, business process maturity, reactive response, and proactive response. Results Using a descriptive-analytical approach and data from 66 managers analyzed via SMART PLS and SPSS, findings indicate that organizations demonstrate moderate levels of strategic monitoring and strategic response, with strong vigilance and proactive response but weak strategic intelligence and resource fluidity. Novelty The study provides an integrated empirical model linking strategic monitoring dimensions with multiple facets of strategic response within delivery companies. Implications The findings suggest that organizations should adopt proactive monitoring systems to improve adaptability, maintain competitive advantage, and strengthen operational resilience in rapidly changing environments. Highlights:• Moderate Adoption of Monitoring Practices Alongside Satisfactory Responsiveness to Environmental Changes• Strong Vigilance and Forward-Looking Actions Contrasted With Limited Intelligence Systems and Resource Flexibility• Need for Systematic Monitoring Approaches to Support Organizational Adaptability and Resilience Keywords: Strategic Monitoring, Strategic Response, Strategic Intelligence, Strategic Vigilance, Delivery Companies